Generation Stress Affecting Students’ Interpersonal Skills at Higher Level - Quratul Ain Hina, Saira Nudrat, Zawar Hussain (PJE, 2023)
The research was designed to assess the level of stress and interpersonal skills of students at higher education level. Further to measure the effect of stress on students’ interpersonal skills of young students. Research was of descriptive-correlational style. The population of the study was based on 9132 social sciences university students (session 2018). 724 students contributed in the data collection. S